Association of provider advice and gestational weight gain in twin pregnancies: a cross-sectional electronic survey - Kara M. WHITAKER; Meghan BARUTH; Rebecca A. SCHLAFF; Christopher P. CONNOLLY; Jihong LIU; Sara WILCOX (BMC Pregnancy and Childbirth, 2020)
Abstract Background Little is known about patient-provider communication on gestational weight gain among women pregnant with twins, a growing population at high risk for adverse maternal and neonatal outcomes. We examined if women’s report of provider advice on gestational weight gain was consistent with the Institute of Medicine (IOM) weight gain guidelines for twin pregnancies, and the association of provider advice on weight gain with women’s weight gain during their twin pregnancy. Methods We conducted a cross-sectional survey of 276 women who delivered twins and received prenatal care in the United States. The 2009 IOM provisional weight gain guidelines for twin pregnancies defined whether provider advice on weight gain and women’s weight gain were below, within, or above guidelines. Multinomial logistic regression examined associations between provider advice on weight gain with women’s weight gain, after adjustment for maternal age, gestational age at delivery, education, parity, twin type, use of assisted reproductive technologies and pre-pregnancy BMI category. Results Approximately 30% of women described provider advice on weight gain below the IOM guidelines, 60% within, and 10% above guidelines. Compared to women who reported weight gain advice within guidelines, women who reported advice below guidelines or who reported no advice were 7.1 (95% CI: 3.2, 16.0) and 2.7 (95% CI: 1.3, 5.6) times more likely to gain less than recommended, respectively. Women who reported provider advice above guidelines were 4.6 (95% CI: 1.5, 14.2) times more likely to exceed guidelines. Conclusions Provider advice on gestational weight gain may be an important predictor of women’s weight gain during twin pregnancies, highlighting the critical need for accurate provider counseling to optimize health outcomes.